On Emblematic Meanings of Traditional Medicinal Herbs: Local Wisdom Values in the Perspective of Culture-Specific Ecopragmatics - R. Kunjana Rahardi (JURNAL ARBITRER, 2020)
The research on emblematic meanings of traditional medicinal herbs is descriptive qualitative research. The data of the research were mostly obtained from texts containing descriptions of local wisdom values found in the names of traditional medicinal herbs. The data were also obtained from the researcher's intuitive ideas as a member of the community where the local wisdom is shared and lived by. The data were obtained by using two methods, namely observation, and speaking methods. The observation method was carried out by using a note-taking technique, while the speaking method was carried out by using the recording technique. The conversation between the researcher and the research informants was recorded and then transcribed to find the required data. The participatory interview method employed an in-depth interview to obtain the description of local wisdom values specifically. The proliferation of data was concluded by classifying and typifying the data after being identified from the sources. Data analysis was carried out using the distributional method with a direct element division technique to cover the linguistic dimensions of this ecopragmatic research. The data was also analyzed and interpreted by using the identity method to cover the pragmatic dimensions in this research. The research results show that: (1) the emblematic meanings are truly found in several traditional medicinal herbs in some parts of Indonesia; (2) the emblematic meanings of the traditional medicinal herbs are classified based on their shapes, uses, directions of the plant's flower, the smell of the plants, and the origins.